Pelatihan Keterampilan Mengolah Sampah Plastik di Yayasan Langkah Kecil Indonesia - Euis Widiati (Jurnal Pengabdian Pada Masyarakat, 2021)
PLASTIC WASTE PROCESSING SKILLS TRAINING AT THE INDONESIAN SMALL STEP FOUNDATION. Waste production is increasing every day in line with the increasing number of products and consumption patterns of society. What must be done to overcome this increase in waste volume is by reducing the volume of waste from its source through community empowerment. In fostering concern for the environment and improving the economy and society, it is necessary to provide skills in the form of handicrafts that are able to process waste into something that has added value and selling value. So that the activity program "Skills Training for Processing Plastic Waste at the Indonesian Small Step Foundation". By providing skills training assistance to members of the Indonesian Small Step Foundation, it can form a spirit of independence and entrepreneurship for these children. So that the main objective in this community service activity program can be achieved, namely in the form of increasing understanding and entrepreneurial abilities in improving the economy and social family.